PENGARUH OWNERSHIP STRUCTURE TERHADAP FIRM PERFORMANCE MELALUI VOLUNTARY DISCLOSURE OF INTELLECTUAL CAPITAL SEBAGAI VARIABEL MEDIASI - Vanesha Gladys Setyono; Saarce Elsye Hatane (Business Accounting Review, 2017)
This study aimed to examine the affect of ownership structure as corporate governance mechanism on voluntary disclosure of intellectual capital and firm performance. In addition, this study also aimed to know the indirect influence of ownership structure on firm performance through voluntary disclosure of intellectual capital as mediating variable. The sample used in this research was 72 manufacturing companies listed on Indonesia Stock Exchange with observation year 2010-2015. The data were collected from the company's annual report and processed by using WarpPLS software version 5.0.The result showed that ownership structure had positive influence on voluntary disclosure of intellectual capital and firm performance and, positive influence of voluntary disclosure of intellectual capital on firm performance. In addition, the study also found that voluntary disclosure of intellectual capital was capable to mediate the influence of ownership structure on firm performance.